2009
DOI: 10.1111/j.1478-3231.2008.01958.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with treatment failure of patients with psychiatric diseases and injecting drug users in the treatment of genotype 2 or 3 hepatitis C chronic infection

Abstract: Patients with a history of depression who were not receiving antidepressants and active IDUs are more likely to fail treatment for genotype 2/3 HCV and will need additional support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 27 publications
(44 reference statements)
2
27
0
2
Order By: Relevance
“…This rate is lower than other reports from tertiary medical centers, referral centers, and clinical trials, where SVR rates have been reported to range between 72% and 89%. [11][12][13][14][15][16]24 One potential reason for the low SVR rate was the high relapse rate (23.5%) in our patient population compared with rates reported by others. Relapse rates in the range of 10% to 15% for genotype 3 are generally reported in the literature.…”
Section: ■■ Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…This rate is lower than other reports from tertiary medical centers, referral centers, and clinical trials, where SVR rates have been reported to range between 72% and 89%. [11][12][13][14][15][16]24 One potential reason for the low SVR rate was the high relapse rate (23.5%) in our patient population compared with rates reported by others. Relapse rates in the range of 10% to 15% for genotype 3 are generally reported in the literature.…”
Section: ■■ Discussionmentioning
confidence: 58%
“…For example, others have reported that patients with various degrees of liver disease, such as cirrhosis, advanced fibrosis, steatosis, and obesity, have lower SVR rates in genotype 3. [11][12][13][14][15][16]25 Age less than 45 years has been associated with improved SVR outcomes in genotype 3. 16 It is increasingly reported that HCV genotype 3 is more difficult to treat than previously thought and is associated with higher rates of complications than most other genotypes.…”
Section: ■■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that cannabis receptor stimulation is associated with lower response to IFN treatment [80]. Moreover, it has been recently reported that patients with a history of depression who were not receiving antidepressants and active intravenous drug users are more likely to fail treatment for HCV genotype 2 or 3 and will need additional support [81].…”
Section: Molecular Epidemiology Of Hcv-relatedmentioning
confidence: 99%
“…An observational study of 20 HCV genotype 2 or 3 patients demonstrated that patients with prior depression who were not on an antidepressant at the beginning of HCV therapy were more likely to drop out and achieved a lower SVR than HCV patients on antidepressants at the beginning of treatment. 58 Selective serotonin re-uptake inhibitors (SSRIs) have been shown to be effective in treating depression in IFN-treated patients. 59 In a study of 15 patients treated with citalopram, 87% responded well to the medication with no change in liver function tests when 10-40 mg/day of the drug was used.…”
Section: Prevention and Treatment Of Ifn-induced Depressionmentioning
confidence: 99%